Superparamagnetic MRI probes for in vivo tracking of dendritic cell migration with a clinical 3 T scanner. (July 2015) - Xu, Ye; Wu, Changqiang; Zhu, Wencheng; Xia, Chunchao; Wang, Dan; Zhang, Houbin; Wu, Jun; Lin, Gan; Wu, Bing; Gong, Qiyong; Song, Bin; Ai, Hua
Abstract: Dendritic cell (DC) based vaccines have shown promising results in the immunotherapy of cancers and other diseases. How to track the in vivo fate of DC vaccines will provide important insights to the final therapeutic results. In this study, we chose magnetic resonance imaging (MRI) to track murine DCs migration to the draining lymph node under a clinical 3 T scanner. Different from labeling immature DCs usually reported in literature, this study instead labeled matured DC with superparamagnetic iron oxide (SPIO) nanoparticle based imaging probes. The labeling process did not show negative impacts on cell viability, morphology, and surface biomarker expression. To overcome the imaging challenges brought by the limitations of the scanner, the size of lymph node, and the number of labeled cell, we optimized MRI pulse sequences. As a result, the signal reduction, caused either by gelatin phantoms containing as low as 12 SPIO-laden cells in each voxel or by the homing SPIO-laden DCs within the draining nodes after footpad injection of only 1 × 10 5 cells, can be clearly depicted under a 3 T MR scanner. Overall, the MRI labeling probes offer a low-toxic and high-efficient MR imaging platform for the assessment of DC-based immunotherapies.